[Better cure for anxiety, sleep disorders, epilepsy?]. - Korpi,ER; Wisden,W; Lüddens,H (Lakartidningen, 1997)
Gamma-aminobutyric acid (GABA), the most important inhibitory neurotransmitter, is characterised by rapid effects that are mediated via GABAA, receptors. These receptors are also targets for many drugs including benzodiazepines, barbiturates and general anaesthetics. Recognition of the heterogeneity of GABAA receptors has opened up new possibilities for the development of more selective therapeutic agents. In particular, subtype-specific receptor ligands varying in intrinsic activity are likely to give rise to fewer side effects than do currently available drugs.